The 100 most cited articles in microplastics: A bibliometric perspective - Muhammad Fitri Yusof; Mohd Fuad Miskon (Journal of Marine Studies, 2026)
This study focused on the 100 most cited articles in microplastic research that were published between 2008 and 2022, with 68% being original research articles and the remainder comprising reviews, short surveys, and other formats. These articles received a total of 113,160 citations, with an average citation density indicating sustained impact. The most cited article received 3,847 citations, while the least cited among the top 100 received 717. These articles appeared in 27 different journals, with Environmental Science and Technology contributing the highest number of publications (n=25) and total citations (n=29,965). The United Kingdom was the most prolific country, producing 25 articles, followed by the United States (n=17) and Germany (n=16). Richard Thompson emerged as the most prominent author, contributing 11 articles with 16,592 citations, while Tamara Galloway demonstrated the highest level of collaboration based on total link strength. Keyword analysis revealed that “microplastics” was the dominant theme, with emerging interests in human health implications, as evidenced by citation density trends. This bibliometric study provides a comprehensive overview of microplastic research, highlighting key journals, authors, institutions, and thematic shifts, thereby facilitating future research directions and collaborations.